Employee Performance Appraisal by Determining Key Performance Indicators Using the Balanced Scorecard Method and Web-Based 360 Degree Feedback - Sari Dwiyanti Tutik; Fauziah; Novi Dian Nathasia (Jurnal Mantik, 2020)
One way to know the performance of an employee is by direct assessment or by filling out an employee performance appraisal questionnaire. But not all companies or factories do that. Only a few companies do this. Therefore, this research is used to make it easier for employees and superiors to jointly know or evaluate their respective performance. The Balanced Scorecard method is a method of measuring company work results or commonly referred to as management strategies. Meanwhile, 360 degree feedback is a tool that provides feedback on the performance of managers, supervisors, superiors. From the results of this study, it can produce an application to apply the Balanced Scorecard method and 360 degrees of feedback into the Employee Performance Appraisal application.